2015
DOI: 10.37335/ijek.v3i1.26
|View full text |Cite
|
Sign up to set email alerts
|

Actual problems of business risk in SME segment. Case study from Slovakia

Abstract: The aim of this article was to define, quantify and compare the significant attributes of business risk for small and medium-sized enterprises (SMEs) in the selected regions of Slovakia. The data was collected through a questionnaire. The whole research was conducted in the Bratislava region on a sample of 102 SMEs, in the region of Trencin on a sample of 105 SMEs and in the Zilina region on a sample of 168 SMEs. Thus we compared important factors of business risk in the most economically developed region of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…Average performance decrease was represented by 15.80% in the Czech Republic (Belás, Macháček et al, 2014). The situation is similar in Slovakia, where market risk was identified as the key risk by the largest number of entrepreneurs and the performance of SMEs compared with pre-crisis period have decreased by at least 15% (Belás, Bilan et al, 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 75%
“…Average performance decrease was represented by 15.80% in the Czech Republic (Belás, Macháček et al, 2014). The situation is similar in Slovakia, where market risk was identified as the key risk by the largest number of entrepreneurs and the performance of SMEs compared with pre-crisis period have decreased by at least 15% (Belás, Bilan et al, 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 75%
“…If an entrepreneur is unwilling to take risk (risk aversion), then he will never be able to realize the talent and spirit of entrepreneurship. Belas et al (2015) conclude that the most important business risk is market risk.…”
Section: Entrepreneur and Risk Profilementioning
confidence: 93%
“…The situation is similar in Slovakia, where it was found out that the most important business risk was market risk (average value of perceived market risk was higher than 50%). (Belás, Bilan, Ključnikov, Vincúrová, and Macháček, 2015) The research results showed that men are slightly more innovative in developing new products and that both genders have the reserved attitudeto the financial investment in the development of new methods and technologies.…”
Section: Results and Short Discussionmentioning
confidence: 99%